PEMANFAATAN JAMUR Beauveria bassiana TERHADAP SERANGGA Aphis sp PADA TANAMAN CABE - Bastian P. Wowiling; Christina Salaki; Henny Makal; Max Tulung (COCOS, 2015)
ABSTRACT Â The study aims to determine the effect of the concentration of spores of the fungus Beauveria bassiana against Aphis sp insect mortality in the laboratory. implementation of the research carried out for three months from July to September 2014. Research using the method Completely Randomized Design (CRD) with four treatments, using B. bassiana spores concentration of 104, 105, 106 and control. Plants used was pepper plants. Each plant with different spore concentrations, in use ten tail pest Aphis sp. Observations on doing every day for one week, with a look at the mortality of each treatment. The results showed that the test insect mortality was highest at day 4 observation with treatment reaches 106 (80%) at follow treatment 105 (52.5%) and treatment of 104 (0%). Observation day 5 mortality in the test insect reaches 106 treatment (20%), then treatment of 105 (32.5%), and treatment of 104 (10%). The results showed that the test insect mortality was highest at day 4 observation with treatment reaches 106 (80%) at follow treatment 105 (52.5%) and treatment of 104 (0%). Observation day 5 mortality in the test insect reaches 106 treatment (20%), then treatment of 105 (32.5%), and treatment of 104 (10%). Observation day 6 the highest mortality of test insects found in treatment reaches 104 (90%), treatment of 105 (15%), and treatment of 106 (0%). In the control mortality was not found, but an increase in population. Â Keywords : Beauveria bassiana, Chili Plants, and Aphis sp